Hypoglycosylation is a common finding in antithrombin deficiency in the absence of a SERPINC1 gene defect. (29th June 2016) - de la Morena‐Barrio, M. E.; Martínez‐Martínez, I.; de Cos, C.; Wypasek, E.; Roldán, V.; Undas, A.; van Scherpenzeel, M.; Lefeber, D. J.; Toderici, M.; Sevivas, T.; España, F.; Jaeken, J.; et al.
Abstract : Essentials We investigated the molecular base of antithrombin deficiency in cases without SERPINC1 defects. 27% of cases presented hypoglycosylation, transient in 62% and not restricted to antithrombin. Variations in genes involved in N‐glycosylation underline this phenotype. These results support a new form of thrombophilia. Click here to listen to Dr Huntington's perspective on thrombin inhibition by the serpins Summary: Background: Since the discovery of antithrombin deficiency, 50 years ago, few new thrombophilic defects have been identified, all with weaker risk of thrombosis than antithrombin deficiency. Objective: To identify new thrombophilic mechanisms. Patients/methods: We studied 30 patients with antithrombin deficiency but no defects in the gene encoding this key anticoagulant ( SERPINC1 ). Results: A high proportion of these patients (8/30: 27%) had increased hypoglycosylated forms of antithrombin. All N‐glycoproteins tested in these patients (α1‐antitrypsin, FXI and transferrin) had electrophoretic, HPLC and Q‐TOF patterns indistinguishable from those of the congenital disorders of glycosylation (rare recessive multisystem disorders). However, all except one had no mental disability. Moreover, intermittent antithrombin deficiency and hypoglycosylation was recorded in five out of these eight patients, all associated with moderate alcohol intake. Genetic analysis, including whole exome sequencing, revealed mutations in different genes involved in the N‐glycosylation pathway. Conclusions: Our study provides substantial and novel mechanistic insights into two disease processes, with potential implications for diagnosis and clinical care. An aberrant N‐glycosylation causing a recessive or transient antithrombin deficiency is a new form of thrombophilia. Our data suggest that congenital disorders of glycosylation are probably underestimated, especially in cases with thrombosis as the main or only clinical manifestation.